Unity in Diversity of Religions in Bumi Flobamora, Indonesia: From Traditional to Modern Pluralism - Jegalus, Norbertus; Atang, Ahmad; Binsasi, Norbertus Antoin (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
The religiously diverse society of NTT (Bumi Flobamora) has received national title as the most tolerant province in Indonesia. However, reality shows that there are religious conflicts, such as the rejection of the establishment of Islamic places of worship and the emergence of various forms of violence with religious nuances. This study attempts to provide a new contemporary social philosophy explanation for the development of religious social conditions. With the help of philosophical methods, the results show that the ideology of pluralism has long lived in Bumi Flobamora. However, this model of